A Dutch validation study of the Multiple Sclerosis Work Difficulties Questionnaire in relapsing remitting multiple sclerosis. Issue 13 (19th June 2021) - van Egmond, Elianne; van Gorp, Dennis; Honan, Cynthia; Heerings, Marco; Jongen, Peter; van der Klink, Jac; Reneman, Michiel; Beenakker, Ernesto; Frequin, Stephan; de Gans, Koen; Hengstman, Gerald; Hoitsma, Elske; et al.
Abstract: Purpose: The current study aimed to evaluate the psychometric properties of the Dutch version of the Multiple Sclerosis Work Difficulties Questionnaire-23 (MSWDQ-23). Methods: Two hundred and thirty-nine employed persons with multiple sclerosis (MS) and 59 healthy controls completed the MSWDQ-23. To verify the factor structure, a confirmatory factor analysis was conducted. To assess construct validity, the MSWDQ-23 scores were correlated to measures of physical disability, fatigue, cognitive and neuropsychiatric problems, depression, health-related quality of life, and work-related variables. MSWDQ-23 scores were compared within different age groups, gender, education levels, and job types. Predictive validity was assessed using a logistic regression analysis to predict a deterioration in employment status after one year based on MSWDQ-23 scores. Results: The internal consistency of the MSWDQ-23 was acceptable ( α  = 0.913, 95% CI = 0.897–0.928) and the results indicated a fair fit. The MSWDQ-23 showed acceptable construct validity, confirming 94% of the hypotheses. The total scale and the psychological/cognitive subscale were able to predict a deterioration in employment status after one year ( χ 2 (1)=18.164, p  < 0.001). Conclusions: The Dutch version of the MSWDQ-23 is a valid and internally consistent instrument to measure self-reported work difficulties in persons with MS. Implications for rehabilitation: The Dutch version of the 23-item Multiple Sclerosis Work Difficulties Questionnaire (MSWDQ-23) is a reliable and valid tool to measure self-reported work difficulties in people with multiple sclerosis (MS). More psychological and cognitive work difficulties are predictive of a deteriorated employment status after one year. The MSWDQ-23 is a helpful tool for researchers and (occupational) health professionals to identify current work difficulties in persons with MS and identify persons at risk for a deterioration in employment one year later.